The Causes and Effects of Anger in Linda Howard’s Novel Death Angel - Chairani, S (KnE Social Sciences, 2018)
The emotion of anger has a long love–hate relationship with morality. On the one hand, anger often motivates us to sanction wrongdoing and uphold demanding moral standards. On the other hand, it can prompt aggression behaviors that are at odds with morality and even lead to moral disasters, such as revenge and even murder. This research is concerned with Anger found in Linda Howard’s novel entitled Death Angel. It can be seen in the novel that the causes of the main characters’ anger are humiliation, infidelity and burglary (theft). All of these causes of anger shown by each of the main characters have effects. The effects are revenge and murder of the main characters themselves. The method used in this study is qualitative research method, that is, a research which uses procedures that make use of qualitative data. The theory of anger used to analyse the data is that of McAllister (2013). The findings of this research constitute the reality that anger must be concerned with the forms of its causes and its effects which are generally and can be confirmed negative. Moreover, the persons overwhelmed with anger usually cannot control his temper that they tend to endanger themselves as well as others with whom they address their anger. Keywords: anger, humiliation, infidelity, burglary, revenge, murder